(untitled) (Asian Journal of Medical and Biological Research, 2017)
Cycloartenyl ferulate (CAF) is a major bioactive phytosteryl ferulate purified from rice bran ?- oryzanol. Previously we reported that CAF ameliorates DSS-induced colitis in mice. The present study was undertaken to investigate the effects of CAF on LPS (lipopolysaccharide) stimulated murine RAW 264.7 macrophages. Immunohistochemistry analysis demonstrated that LPS (10ng/mL) treatment exhibited nuclear translocation of NF-?B-p65 in RAW macrophages, which was markedly inhibited CAF (30?M). LPS (10ng/mL) stimulation for 1-4 hours significantly upregulated iNOS and COX-2 mRNA in RAW 264.7 macrophages, but COX-2 mRNA was faster than that of iNOS mRNA. Macrophages pretreated with CAF greatly inhibited the LPS stimulated iNOS mRNA in a dose dependent manner (1-30?M), but CAF weakly inhibited COX-2 mRNA. Interestingly, CAY 10404 (COX-2 inhibitor) inhibited LPS stimulated iNOS mRNA, but not COX-2. In addition, PGE2 (1?M) upregulated iNOS mRNA but did not show any remarkable effects on NF-?B-p65 nuclear translocation in RAW macrophages. PD98059 (p44/42 MAP kinase inhibitor) inhibited iNOS mRNA, but not COX-2. On the other hand, PD169316 (p38 MAP kinase inhibitor) neither inhibited iNOS mRNA nor COX-2. Our results suggest that iNOS mRNA expression by LPS is mediated via p44/42 MAP kinase pathway in RAW 264.7 macrophages, which depends on the preceding expression of COX-2 expression. CAF downregulates iNOS mRNA via an inhibition of nuclear translocation of NF-?B with different mode of action on COX-2 gene expression. Asian J. Med. Biol. Res. December 2016, 2(4): 523-531